The impact of endometriosis on female athletes’ lives and wellbeing : a qualitative study : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University, Auckland, Aotearoa/New Zealand - Klingenberg, Kirstie (Massey University, 2022)
Endometriosis is a disease characterised by chronic pelvic pain and has a prevalence of around 8% in athletes. This study aimed to explore the experiences of athletes with endometriosis and the impact on their lives. Endometriosis is known to be incredibly burdensome for women, but this has not yet been explored specifically in athletes. Nine (9) women with a surgical diagnosis of endometriosis participated in semi-structured interviews, which were recorded and transcribed. Critical realism and feminist theory informed the approach. This data was analysed using reflexive thematic analysis, and four themes were developed. Firstly, Theme One: “A Cloud Over You” The Burden of Endometriosis, details the burden of endometriosis on athletes and how chronic pain impacted almost every area of their lives, including training, performance, and mental health. Theme Two: “How was your Holiday?” Experiences of Invalidation and Minimisation describes the attitudes and lack of empathy that participants were subjected to from healthcare practitioners (HCP), their coaches and support staff, and for some, their social supports. Theme Three: Recognising “Maybe This Isn’t Normal” Advocacy and Overcoming evaluates the time when each participant realised in some way that what they were experiencing was not normal, which caused them to seek more help. This theme also details the self-advocacy required to achieve substantial change. Finally, Theme Four: “Thank God I’ve Got an Answer” Misdiagnoses, Diagnoses and Treatments, describes the difficulties participants experienced in seeking help. This study illustrates not only the need for future research on athletes with endometriosis, but also for improved attitudes and awareness for those working with athletes.
Keywords: 520304 Health psychology